Evaluation of Patients Receiving Intravitreal Antivascular Endothelial Growth Factor for Diabetic Macular Edema in Clinical Practice in the United States. (March 2021) - Pitcher, John D.; Moshfeghi, Andrew A.; Lucas, Genevieve; Boucher, Nick; Moini, Hadi; Saroj, Namrata
Purpose: We assessed the effect of treatment frequency with intravitreal antivascular endothelial growth factor (anti-VEGF) agents on visual acuity (VA) in diabetic macular edema (DME). Methods: This retrospective analysis assessed electronic medical records of eyes newly diagnosed with DME and treated with an anti-VEGF agent at US clinics using the Vestrum Health (Naperville, Illinois) treatment and outcomes database. Eyes were divided into 2 injection frequency subcohorts (≤ 6 vs > 6 injections/y); treatment frequency and change in mean VA (Early Treatment Diabetic Retinopathy Study letters) were evaluated. Results: Among 155 240 eyes assessed, 3028 met inclusion criteria for analysis in year 1 and 1292 in year 2. During year 1 of treatment, 57% (n = 1725) received > 6 injections; most continued to receive the same injection frequency during year 2. Mean VA gain from baseline at year 1 was lower in the ≤ 6 than in the > 6 injections/year subcohort (3.7 vs 8.0 letters, respectively; P < .001). Mean VA change from the end of year 1 to year 2 for eyes receiving ≤ 6 injections in year 1 generally remained unchanged, irrespective of year 2 dosing frequency. In eyes that received > 6 injections in year 1, mean VA loss was significantly greater for eyes receiving less-frequent dosing in year 2 than in those maintained on > 6 injections. Conclusions: More than 50% of eyes with DME in routine clinical practice that completed at least 1 year of follow-up received > 6 injections of an anti-VEGF agent during the first year, resulting in better VA gains than eyes treated less frequently.